2017
DOI: 10.1002/term.2511
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet lysate supports the formation of robust human periodontal ligament cell sheets

Abstract: The use of stem cell-derived sheets has become increasingly common in a wide variety of biomedical applications. Although substantial evidence has demonstrated that human platelet lysate (PL) can be used for therapeutic cell expansion, either as a substitute for or as a supplement to xenogeneic fetal bovine serum (FBS), its impact on cell sheet production remains largely unexplored. In this study, we manufactured periodontal ligament stem cell (PDLSC) sheets in vitro by incubating PDLSCs in sheet-induction med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Based on qRT‐PCR, immunofluorescent staining of transverse images and Western blotting, we found that CM1‐ and CM2‐based inductive media significantly elevated the abundance of fibronectin, COL‐1 and integrin β1 protein (Figs C–E and A–E). In our previous study, periodontal ligament stem cell (PDLSC) sheets were manufactured in vitro by incubating cells in sheet‐induction media supplemented with various ratios of human platelet lysate (PL) and xenogeneic FBS, and immunohistochemical staining suggested that all resultant cellular materials displayed similar protein profiles of fibronectin, COL‐1 and integrin β1 . Thus, it appears that immunohistochemical staining of lateral sections is not necessary to evaluate the protein profiles of stem cell sheets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on qRT‐PCR, immunofluorescent staining of transverse images and Western blotting, we found that CM1‐ and CM2‐based inductive media significantly elevated the abundance of fibronectin, COL‐1 and integrin β1 protein (Figs C–E and A–E). In our previous study, periodontal ligament stem cell (PDLSC) sheets were manufactured in vitro by incubating cells in sheet‐induction media supplemented with various ratios of human platelet lysate (PL) and xenogeneic FBS, and immunohistochemical staining suggested that all resultant cellular materials displayed similar protein profiles of fibronectin, COL‐1 and integrin β1 . Thus, it appears that immunohistochemical staining of lateral sections is not necessary to evaluate the protein profiles of stem cell sheets.…”
Section: Discussionmentioning
confidence: 99%
“…Haematoxylin and eosin staining was performed, and the stained sheets were analysed using previously reported methods . Briefly, cell sheets were fixed in 4% paraformaldehyde for 12 hrs.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 However, a literature search revealed only one report that investigated the effect of HPL on hPDLSCs. 27 In that study, HPL was added into the culture medium, without being delivered via a scaffold. The HPL beneted the matrix production by the hPDLSCs, the osteogenic gene expressions were upregulated, and the mineralization of hPDLSCs was increased.…”
Section: Introductionmentioning
confidence: 99%
“…HPL was suggested to alter the ASC behavior and function via multiple signaling pathways (Kakudo et al, 2019). A previous study showed that HPL can benefit cell behavior and ECM production, thus optimizing the conditions for cell sheet production in periodontal ligament stem cells (Tian et al, 2018). Since the application of HPL in fabricating ASC sheets had not been reported in the literature, it was therefore intriguing to explore the effect of replacing FBS with HPL on the microenvironment fabricated within ASC sheets.…”
Section: Introductionmentioning
confidence: 99%